The place of subfascial endoscopic perforator vein surgery (SEPS) in advanced chronic venous insufficiency treatment - Wiesław Pesta; Waldemar Kurpiewski; Marek Kowalczyk; Rafał Szynkarczuk; Magdalena Łuba; Anna Żurada; Radosław Grabysa (Videosurgery and Other Miniinvasive Techniques)
In spite of medical science development and initiation of new technologies in minimally invasive surgery, treatmentof advanced chronic venous insufficiency at the 5th and 6th degree of CEAP classification is still a great clinical challenge.In case of no satisfactory results of non-surgical treatment of recurrent venous ulcers, scientists search for alternativetherapeutic methods which could be more effective and lasting. Subfascial endoscopic perforator vein surgery(SEPS) as a method of reducing venous pressure in the superficial venous system could provide healing of the recurrentvenous ulcer. In this study we present a review of contemporary opinions about the place and significance of subfascialendoscopic perforator vein surgery as a treatment of advanced chronic venous insufficiency.